Phytotoxic activity of extracts obtained from cagaita (Eugenia dysenterica DC. - Myrtaceae) on the growth of black-jack (Bidens pilosa L.) - Ribeiro, Marlene Benedita; Malheiros, Rafael Soares Pozzi; Machado, Luciana Lucas; Mapeli, Ana Maria (Iheringia, Série Botânica., 2020)
Cagaita (Eugenia dysenterica) is a native plant of the Cerrado with great economic, social and environmental importance. The objective of this work was to determine the phytotoxic potential of extracts of leaf and bark from the stem of E. dysenterica on the initial growth of B. pilosa (black-jack). The experiment was performed under laboratory conditions, and the extracts used were: leaf aqueous extract, leaf ethanolic extract, leaf hydroalcoholic extract 70:30, leaf hydroalcoholic extract 50:50, bark from the stem aqueous extract, bark from the stem ethanol extract, bark from the stem hydroalcoholic extract 70:30 and bark from the stem hydroalcoholic extract 50:50. All E. dysenterica leaf and bark from the stem extracts exerted inhibitory effects on the radicle and hypocotyl growth of black-jack seedlings. Thus, E. dysenterica leaf and bark from the stem extracts present high phytotoxic potential and may be useful in studies attempting to find new molecules with bioherbicidal function for controlling spontaneous plants.